Monte Carlo simulation of a container terminal project investment decision . - Neel, Mark Anthony (My University, 2017)
The objective of this paper has been to investigate the ability of Monte Carlo simulation to mitigate the adverse effects of ‘planning fallacy’ for large container terminal investment decisions which are based upon discounted cash flow analysis. Company executives are mandated to grow the economic value of their organisations. One key growth avenue for executives, is that of portfolio expansion, by investing in financially attractive new operations in order to achieve long-term economic company growth. This notion is further complicated for the container terminal industry, where opportunities for new container terminal developments are continuously diminishing due to their inherent topographical and geographical requirements. This scarcity of potential projects leads to much contention for investment appraisals, where project risk is often downplayed due to the element of ‘planning fallacy’. This becomes an ever more critical concern when considering the vast capital requirements of a container terminal project, where in some cases the total expenditure approaches USD 3 billion (World Bank, 2016). These investments are typically analysed using discounted cash flows, with the net present value outcome used as the criterion for the investment decision. The chief limitation of this form of financial investment appraisal is its inability to provide insight into the project’s risk profile, hence this investigation’s focus on the ability of Monte Carlo simulation to provide an exhaustive view of project risk and thereby mitigate the element of ‘planning fallacy’ for container terminal investment decisions. This paper is based upon an actual container terminal investment case, which used discounted cash flows and net present value as its decision criterion. The investigation then built upon the discounted cash flow model provided and used Monte Carlo simulation to provide an insight into the risk profile of the project. The simulation’s results were then contrasted to those provided by other risk assessment methods. The investigation found that while Monte Carlo simulation cannot provide a clear ‘accept’ or ‘reject’ decision outcome, it did provide a clear view of the project’s inherent risk, which the other risk assessment tools of sensitivity and scenario analysis could not clearly articulate. Although the project which was used for this paper’s investigation warranted an ‘accept’ decision based on the net present value criterion, the results of the Monte Carlo simulation found an ‘accept’ decision would be imprudent due to the low probability that the project would in fact create economic value. All investment decisions duly require exhaustive consideration and very few are more so deserving than that of container terminal investment decisions. It would be irresponsible for executives not to consider Monte Carlo simulation for project risk appraisal, as Monte Carlo simulation provides colour to a previously black and white decision.
MBA Thesis
Keywords: Finance -- Mathematical models,Investments ,Risk management,Monte Carlo method